Multivariate morphometric differentiation between females of two cryptic species of Lutzomyia subgenus Helcocyrtomyia (Diptera: Psychodidae) - CAZORLA-P., DALMIRO (Revista Colombiana de Entomología, 2009)
The vectorial capacity of sibling species of the Neotropical genus Lutzomyia is likely to differ, thus a means of identifying the most important vector species is of critical importance to the epidemiology and control of the leishmanioses. Multivariate statistical procedures were employed to determine whether the females of two sibling sandfly species (genus Lutzomyia) of the subgenus Helcocyrtomyia, L. ceferinoi (N= 31) and L. erwindonaldoi (N= 32), can be discriminated on the basis of quantitative metric characters. Size independent discriminant analysis compared a set of three morphological characters of the wing (length of veins δ and α, and width of wing) measured from known specimens to detect differences between the two species. Morphometric discriminant analysis allowed differentiation of the females of both species with a high degree of accuracy (canonical correlation = 0.97; P